Association between temperature variability and global meningitis incidence. (January 2023) - Chen, Junjun; Jiao, Zhihua; Liang, Zhisheng; Ma, Junxiong; Xu, Ming; Biswal, Shyam; Ramanathan, Murugappan; Sun, Shengzhi; Zhang, Zhenyu
Highlights: Australasia, central sub-Saharan Africa, and high-income North America are identified to be most susceptible to meningitis due to temperature variability changes. Males, children, and elderly are more vulnerable to temperature-related meningitis incidents. Compared to high emission (SSP585), low emission (SSP126) scenario can reduce a median of 85.8% of future meningitis incidence globally. Abstract: Background: Meningitis can cause devastating epidemics and is susceptible to climate change. It is unclear how temperature variability, an indicator of climate change, is associated with meningitis incidence. Methods: We used global meningitis incidence data along with meteorological and demographic data over 1990–2019 to identify the association between temperature variability and meningitis. We also employed future (2020–2100) climate data to predict meningitis incidence under different emission levels (SSPs: Shared Socioeconomic Pathways). Results: We found that the mean temperature variability increased by almost 3 folds in the past 30 years. The largest changes occurred in Australasia, Tropical Latin America, and Central Sub-Saharan Africa. With a logarithmic unit increase in temperature variability, the overall global meningitis risk increases by 4.8 %. Australasia, Central Sub-Saharan Africa, and High-income North America are the most at-risk regions. Higher statistical differences were identified in males, children, and the elderly population. Compared to high-emission (SSP585) scenario, we predicted a median reduction of 85.8 % in meningitis incidence globally under the low-emission (SSP126) climate change scenario by 2100. Conclusion: Our study provides evidence for temperature variability being in association with meningitis incidence, which suggests that global actions are urgently needed to address climate change and to prevent meningitis occurrence.